Sativex® as add-on therapy vs. further optimized first-line ANTispastics (SAVANT) in resistant multiple sclerosis spasticity: a double-blind, placebo-controlled randomised clinical trial - Markovà, Jolana; Essner, Ute; Akmaz, Bülent; Marinelli, Marcella; Trompke, Christiane; Lentschat, Arnd; Vila, Carlos (International Journal of Neuroscience, 2019)
Purpose/aim: To evaluate the efficacy of tetrahydrocannabinol (THC):cannabidiol (CBD) oromucosal spray (Sativex®) as add-on therapy to optimised standard antispasticity treatment in patients with moderate to severe multiple sclerosis (MS) spasticity. METHODS: Sativex® as add-on therapy vs. further optimised first-line ANTispastics (SAVANT) was a two-phase trial. In Phase A, eligible patients received add-on THC:CBD spray for 4 weeks to identify initial responders [≥20% improvement from baseline in spasticity 0-10 numerical rating scale (NRS) score]. Following washout, eligible initial responders were randomised to receive THC:CBD spray or placebo for 12 weeks (double-blinded, Phase B). Optimisation of underlying antispasticity medications was permitted in both groups across all study periods. RESULTS: Of 191 patients who entered Phase A, 106 were randomised in Phase B to receive add-on THC:CBD spray (n = 53) or placebo (n = 53). The proportion of clinically relevant responders after 12 weeks (≥30% NRS improvement; primary efficacy endpoint) was significantly greater with THC:CBD spray than placebo (77.4 vs. 32.1%; p < 0.0001). Compared with placebo, THC:CBD spray also significantly improved key secondary endpoints: changes in mean spasticity NRS (p < 0.0001), mean pain NRS (p = 0.0013), and mean modified Ashworth's scale (p = 0.0007) scores from Phase B baseline to week 12. Adverse events, when present, were mild/moderate and without new safety concerns. CONCLUSIONS: Add-on THC:CBD oromucosal spray provided better and clinically relevant improvement of resistant MS spasticity compared with adjusting first-line antispasticity medication alone.
Keywords: parasympatolytika; Humans; Dronabinol; lidé středního věku; fixní kombinace léků; Multiple Sclerosis; Double-Blind Method; Female; výsledek terapie; dvojitá slepá metoda; lidé; tetrahydrokanabinol; ženské pohlaví; roztroušená skleróza; Male; Muscle Spasticity; Middle Aged; Treatment Outcome; svalová spasticita; Parasympatholytics; Cannabidiol; Drug Combinations; mužské pohlaví; prospektivní studie; kombinovaná farmakoterapie; kanabidiol; Drug Therapy, Combination; Prospective Studies